Terror in the Classroom: Teaching Terrorism Without Terrorizing - Pinar Alakoc, Burcu (Journal of political science education, 2019)
Despite its popularity among students, terrorism is a sensitive and emotive topic that is difficult to learn, and challenging to teach. Given the lack of a simple definition, terrorism is hard to explain objectively and comprehensively. Perceptually value-laden and provocative, it can reinforce stereotypes and prejudices against a group of people generating conflicting emotional reactions in the classroom. The disturbingly violent nature of the subject can also be hard to communicate to students while staying calm and professional. Additionally, it is a subject where interactive methods cannot easily be incorporated, and the use of humor may come out as inappropriate and abrasive to different audiences. Taking these as a point of departure, this article draws on my experiences as a researcher and professor of terrorism to illustrate the ways in which these challenges can be mitigated. Overall, the article provides examples and strategies to help instructors not terrorize or be terrorized while teaching sensitive and controversial subjects such as terrorism.